Development of Aluminium Boiling Pot Incorporated with Fractally Generated Internal Cylindrical Fins - Olabisi, O. I.; Salau, T. A. O.; Ajide, O. O. (Archives of Current Research International, 2025)
Aluminium boiling pots as typical in heated liquid-filled vessels are indispensable for heating purposes especially for domestic water boiling. Available information on its current design showed that it required prolonged heating duration, leading to high consumption of fuel such as Liquefied Petroleum Gas (LPG). Internal cylindrical fins are used in heated liquid-vessels, but with limited heat transfer enhancement. Fractal induced surfaces being self-similar geometrical-objects have high potential for heat transfer enhancement, but there is dearth of information in their use for aluminium boiling pot’s integrated with internal cylindrical fins. Therefore, a 7-litre Experimental Aluminium Boiling Pot (EABP) and internal cylindrical fins (Ø5×140 mm) were designed and fabricated in this study. The EABP had base-thickness, height, internal-diameter and external-diameter of 10, 155, 258 and 274 mm, respectively and 121 fractal placement locations for the internal cylindrical fins. The chemical constituents of all the critical elements in the aluminium used to fabricate the EABP and the internal cylindrical fins fall within the allowable composition for food grade aluminium. Hence, the use of the EABP for boiling water poses no danger to human health. The pot performance when filled with liquid and containing selected number of internal cylindrical fins placed according to affine rules can be evaluated for arbitrary Iterated Fractal System (IFS). The EABP when incorporated with fractally positioned internal cylindrical fins will provide solutions for household sectors on how water heating can be done faster with minimal LPG’s cost.